Representasi Digital Secara Semantik dari Warisan Budaya Bali: Studi Kasus pada Kain Tenun Gringsing - Awidya, Duta; Astuti, Luh Gede; Pramartha, Cokorda; Ari Mogi, I Komang (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 2 (2024): JELIKU Volume 13 No 2, November 2024DO - 10.24843/JLK.2024.v13.i02.p06, 2024)
Gringsing cloth, a unique and traditional Balinese textile, is facing significant preservation challenges, particularly in the digital age where documentation and accessibility are limited. This study addresses these issues by developing a digital documentation system for Gringsing cloth using an ontology-based approach to manage and organize its complex information. The study followed the Design Science Research Methodology (DSRM), identifying key problems and setting objectives to preserve and enhance the accessibility of Gringsing knowledge. The system was designed based on interviews with Gringsing producers and an extensive literature review. Utilizing Methontology, an ontology was created to capture essential aspects of the cloth, including motifs, colors, sizes, and their cultural uses. The web-based system was developed using Semantic Web technologies, ensuring accurate information retrieval through SPARQL queries. The system was tested with 30 users using Black-box Testing to verify its functionality. Furthermore, an evaluation with the Technology Acceptance Model (TAM) revealed positive feedback regarding ease of use and perceived usefulness, highlighting the system’s practicality and its potential benefit for preserving the Gringsing tradition.